PENGARUH EFIKASI DIRI TERHADAP PROKRASTINASI DALAM MENGERJAKAN SKRIPSI PADA MAHASISWA PENDIDIKAN MASYARAKAT FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU - Zidan, Zidan; Azhar, Azhar; Fitrilinda, Dafetta (STKIP Pesisir Selatan, 2026)
This study aims to analyze the effect of self-efficacy on procrastination in thesis writing among students of the Community Education Study Program, Faculty of Teacher Training and Education, Universitas Riau. Self-efficacy is considered an important psychological factor that determines academic success, while procrastination is a common obstacle that hinders students’ progress. The study employed a quantitative survey design. The participants were final-year students of the Community Education Study Program, selected using purposive sampling. The instruments consisted of a self-efficacy scale based on Bandura’s theory and an academic procrastination scale developed by Ferrari. Data were analyzed using regression analysis to examine the effect of self-efficacy on procrastination. Preliminary findings indicate that most students tend to have moderate to low levels of self-efficacy, while their academic procrastination levels are relatively high. Statistical analysis revealed a significant negative relationship between self-efficacy and procrastination, suggesting that students with higher self-efficacy are less likely to procrastinate. This study contributes to the body of knowledge by contextualizing the relationship between self-efficacy and procrastination in Community Education students at Universitas Riau, an area that has not been widely explored. The findings are expected to serve as a basis for developing academic guidance strategies aimed at enhancing students’ self-efficacy and reducing academic procrastination.